Sciatic neuropathy caused by a pressure ulcer: A case report. Issue 36 (September 2018) - Hwang, Jae Ha; Kim, Dong Wan; Kim, Kwang Seog; Lee, Sam Yong
Abstract: Rationale: Sciatic neuropathy has various causes; however, cases in which a pressure ulcer led to sciatic neuropathy have not been reported to date. Patient concerns: A 33-year-old woman with no pre-existing mobility problems visited our department with the chief complaint of an extensive pressure ulcer and necrosis in her right buttock. She had a medical history of being bedridden for 2 days while in a coma due to a drug overdose 2 months previously. Physical examination revealed loss of sensation and foot drop in the right foot. Diagnosis: Physical examination, magnetic resonance imaging, and nerve conduction studies were conducted; the patient was diagnosed with a common peroneal branch injury of the right sciatic nerve. Interventions: The necrotic tissue was debrided and sciatic nerve decompression was performed, followed by frequent dressing changes. In addition, psychiatric treatment and physical therapy were performed simultaneously. Outcomes: The pressure ulcer decreased in size and healed to some extent with granulation tissue. However, gait disorders, accompanied by symptoms of sciatic neuropathy, continued. The patient was transferred to the department of gastroenterology for the treatment of toxic hepatitis, which occurred during her inpatient treatment. Lessons: Physicians should be aware that sciatic neuropathy may occur during the treatment of patients with a pressure ulcer who exhibit no symptoms of paraplegia or quadriplegia. To prevent neuropathy, aggressive treatment of the pressure ulcer is necessary.